The FLIPPED STEP study: A randomized controlled trial of flipped vs. traditional classroom teaching in a university-level statistics and epidemiology course - Lene Berge Holm; Andre Rognes; Fredrik Andreas Dahl (International Journal of Educational Research Open, 2022)
A flipped classroom, also known as flipped learning, is a teaching method in which students watch online lectures at home, followed by group work in the classroom. This study aimed to evaluate the efficacy of a flipped classroom vs. traditional lectures in a statistics and epidemiology course at Oslo Metropolitan University. The study used a pragmatic randomized controlled trial design in which one group of students received traditional lectures, while another group received flipped classroom teaching. Each participating student had previous experience with both teaching methods. No difference was found in exam grades between the two groups, but the students preferred the flipped classroom significantly (p = .008). Students who received instruction in the flipped classroom preferred this method to a higher degree than those who received traditional lectures (p = .018).